A novel adaptable finger rehabilitation device - Rogério Sales Gonçalves; Paulo Eduardo Ferreira da Silva; Guênia Mara Vieira Ladeira; Giuseppe Carbone; Marco Ceccarelli (International Journal of Advanced Robotic Systems)
Human fingers are essential for many everyday activities, making them vulnerable to a variety of injuries. Finger rehabilitation may be required to restore key functions like range of motion, strength, agility, neurological recovery, and pain relief, especially after events like a stroke. Besides several rehabilitation devices being investigated, there is still a need for a reliable and user-friendly solution. Thus, this paper presents the first steps in the development of an innovative mechanism for rehabilitation of the human finger that allows flexion and extension of individual movements of each phalanx or combined movements for each finger. The proposed device consists of an exoskeleton with an articulated mechanism placed on each finger. The mechanical structure for moving each phalanx consists of a six-bar articulated mechanism with a slider, whose movement is made by a linear actuator. The design process is carefully described, starting from the finger kinesiology, followed by a kinematic modeling of the proposed device, 3D CAD modeling, and the construction of a prototype to index finger, including its control architecture. Both simulations and experimental tests are carried out, showing a suitable behavior of the proposed device in performing both individual and combined flexion/extension exercises of a human finger.